Pengaruh Akuntabilitas Dan Transparansi Terhadap Kualitas Pengelolaan Keuangan Pada Bappelitbangda Kabupaten Sukabumi - Wulandari, Sri; Eriswanto, Elan (Universitas Dian Nuswantoro, 2023)
The Effect of Accountability and Transparency on the Quality of Financial Management is the subject of this research. To collect data, observations and questionnaires with an ordinal Likert scale were used to process research data. This study used an associative method with a quantitative approach. The population in this study were heads, secretaries, treasurers, heads of fields, and group positions in the Regional Development Planning, Research and Development Agency of Sukabumi Regency. The sampling technique used is nonprobability sampling with saturated sampling technique, namely the entire population is used as a sample, totaling 42 samples. The test results using SPSS 25 For Windows, partially show that accountability has a positive effect on the quality of financial management of 5.698 and a significant of 0.000, transparency has a positive effect on the quality of financial management of 9.451 and a significant of 0.000. The simultaneous test results show that accountability and transparency have a positive effect on the quality of financial management of 43.587 and a significant value of 0.000.